# Service for Solving Linear Programming Problems

and other interesting typical problems
Ðóññêèé

## Example ¹3. Finding the Determinant of a 5x5 Matrix

This solution was made using the calculator presented on the site.
Let's calculate the determinant A using a elementary transformations.
 det A = 4 1 1 2 1 = 1 2 -1 1 1 3 1 1 1 1 2 1 1 4 1 2 -1 1 1 5
The elements of row 3 multiplied by -1 are added to the corresponding elements of row 1.   more info
 4 + 3 * ( -1) 1 + 1 * ( -1) 1 + 1 * ( -1) 2 + 1 * ( -1) 1 + 1 * ( -1) 1 2 -1 1 1 3 1 1 1 1 2 1 1 4 1 2 -1 1 1 5
This elementary transformation does not change the value of the determinant.
 = 1 0 0 1 0 = 1 2 -1 1 1 3 1 1 1 1 2 1 1 4 1 2 -1 1 1 5
The elements of column 4 multiplied by -1 are added to the corresponding elements of column 1.   more info
 1 + 1 * ( -1) 0 0 1 0 1 + 1 * ( -1) 2 -1 1 1 3 + 1 * ( -1) 1 1 1 1 2 + 4 * ( -1) 1 1 4 1 2 + 1 * ( -1) -1 1 1 5
This elementary transformation does not change the value of the determinant.
 = 0 0 0 1 0 = 0 2 -1 1 1 2 1 1 1 1 -2 1 1 4 1 1 -1 1 1 5
 0 0 0 1 0 0 2 -1 1 1 2 1 1 1 1 -2 1 1 4 1 1 -1 1 1 5
Row number 1
Column number 1
Element Row 1 and column 1
have been deleted
( -1) 1 + 1 * 0 *
 2 -1 1 1 1 1 1 1 1 1 4 1 -1 1 1 5
 0 0 0 1 0 0 2 -1 1 1 2 1 1 1 1 -2 1 1 4 1 1 -1 1 1 5
Row number 1
Column number 2
Element Row 1 and column 2
have been deleted
( -1) 1 + 2 * 0 *
 0 -1 1 1 2 1 1 1 -2 1 4 1 1 1 1 5
 0 0 0 1 0 0 2 -1 1 1 2 1 1 1 1 -2 1 1 4 1 1 -1 1 1 5
Row number 1
Column number 3
Element Row 1 and column 3
have been deleted
( -1) 1 + 3 * 0 *
 0 2 1 1 2 1 1 1 -2 1 4 1 1 -1 1 5
 0 0 0 1 0 0 2 -1 1 1 2 1 1 1 1 -2 1 1 4 1 1 -1 1 1 5
Row number 1
Column number 4
Element Row 1 and column 4
have been deleted
( -1) 1 + 4 * 1 *
 0 2 -1 1 2 1 1 1 -2 1 1 1 1 -1 1 5
 0 0 0 1 0 0 2 -1 1 1 2 1 1 1 1 -2 1 1 4 1 1 -1 1 1 5
Row number 1
Column number 5
Element Row 1 and column 5
have been deleted
( -1) 1 + 5 * 0 *
 0 2 -1 1 2 1 1 1 -2 1 1 4 1 -1 1 1
Products are summed. If the element is zero then product is zero too.
 = ( -1) 1 + 4 * 1 * 0 2 -1 1 = 2 1 1 1 -2 1 1 1 1 -1 1 5
 = - 0 2 -1 1 = 2 1 1 1 -2 1 1 1 1 -1 1 5
The elements of row 2 multiplied by -1 are added to the corresponding elements of row 3.   more info
 0 2 -1 1 2 1 1 1 -2 + 2 * ( -1) 1 + 1 * ( -1) 1 + 1 * ( -1) 1 + 1 * ( -1) 1 -1 1 5
This elementary transformation does not change the value of the determinant.
 = - 0 2 -1 1 = 2 1 1 1 -4 0 0 0 1 -1 1 5
 0 2 -1 1 2 1 1 1 -4 0 0 0 1 -1 1 5
Row number 3
Column number 1
Element Row 3 and column 1
have been deleted
( -1) 3 + 1 * -4 *
 2 -1 1 1 1 1 -1 1 5
 0 2 -1 1 2 1 1 1 -4 0 0 0 1 -1 1 5
Row number 3
Column number 2
Element Row 3 and column 2
have been deleted
( -1) 3 + 2 * 0 *
 0 -1 1 2 1 1 1 1 5
 0 2 -1 1 2 1 1 1 -4 0 0 0 1 -1 1 5
Row number 3
Column number 3
Element Row 3 and column 3
have been deleted
( -1) 3 + 3 * 0 *
 0 2 1 2 1 1 1 -1 5
 0 2 -1 1 2 1 1 1 -4 0 0 0 1 -1 1 5
Row number 3
Column number 4
Element Row 3 and column 4
have been deleted
( -1) 3 + 4 * 0 *
 0 2 -1 2 1 1 1 -1 1
Products are summed. If the element is zero then product is zero too.
 = - ( ( -1) 3 + 1 * ( -4) * 2 -1 1 ) = 1 1 1 -1 1 5
 = 4 * 2 -1 1 = 1 1 1 -1 1 5
The elements of row 2 multiplied by -1 are added to the corresponding elements of row 3.   more info
 2 -1 1 1 1 1 -1 + 1 * ( -1) 1 + 1 * ( -1) 5 + 1 * ( -1)
This elementary transformation does not change the value of the determinant.
 = 4 * 2 -1 1 = 1 1 1 -2 0 4
 2 + 1 -1 + 1 1 + 1 1 1 1 -2 0 4
This elementary transformation does not change the value of the determinant.
 = 4 * 3 0 2 = 1 1 1 -2 0 4
 3 0 2 1 1 1 -2 0 4
Row number 1
Column number 2
Element Row 1 and column 2
have been deleted
( -1) 1 + 2 * 0 *
 1 1 -2 4
 3 0 2 1 1 1 -2 0 4
Row number 2
Column number 2
Element Row 2 and column 2
have been deleted
( -1) 2 + 2 * 1 *
 3 2 -2 4
 3 0 2 1 1 1 -2 0 4
Row number 3
Column number 2
Element Row 3 and column 2
have been deleted
( -1) 3 + 2 * 0 *
 3 2 1 1
Products are summed. If the element is zero then product is zero too.
 = 4 * ( -1) 2 + 2 * 1 * 3 2 = -2 4
 = 4 * 3 2 = -2 4
= 4 * ( 3 * 4 - 2 * ( -2) ) =
= 4 * ( 12 + 4 ) =
= 64